1979
DOI: 10.3171/jns.1979.51.6.0812
|View full text |Cite
|
Sign up to set email alerts
|

Communicating hydrocephalus as a cause of aqueductal stenosis

Abstract: Eleven cases of presumed aqueductal stenosis with onset of symptoms after the first decade were reviewed. Ten patients had complete occlusion and one a high-grade stenosis. In 10, the dilated lateral ventricles caused a marked inferior displacement of the third ventricle. Postshunting diagnostic studies on six of these patients revealed ascent of the third ventricle, and in three of these the aqueduct was shown to be patent. It appears that in some cases of advanced communicating hydrocephalus the descending t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(17 citation statements)
references
References 15 publications
1
15
0
1
Order By: Relevance
“…Another hypothesis (24) argues that AS is a secondary phenomena to an initially communicating hydrocephalus and results from a compression of the midbrain that obstructs the aqueduct (25)(26)(27).…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
“…Another hypothesis (24) argues that AS is a secondary phenomena to an initially communicating hydrocephalus and results from a compression of the midbrain that obstructs the aqueduct (25)(26)(27).…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
“…16) Knol et al 9) suggested a greater enlargement of the third than of the fourth ventricle is compatible with a CSF block not only intraventricular but also in the subarachnoid space. Nugent et al 12) reported even communicating hydrocephalus may cause a secondary occlusion of aqueduct. AS cannot explain all the triventriculomegaly and its diagnosis should be decided quite deliberately.…”
Section: Discussionmentioning
confidence: 99%
“…Head trauma, a small subarachnoid hemorrhage or a viral infection with benign meningitis have all been claimed as anatomic causes of aqueductal stenosis decompensation (Cinalli et al 2004a, Jellinger, 1986, Lapras et al 1986. A functional mechanism might also contribute: progressive enlargement of the lateral and third ventricles would lead to a distortion of the brainstem and kinking of the aqueduct (Nugent et al 1979, Raimondi et al 1976). …”
Section: Primary Aqueductal Stenosismentioning
confidence: 99%